Autophagosome immunoisolation from GFP-LC3B mouse tissue. Issue 2 (1st February 2019) - Yao, Jingyu; Qiu, Yaoyan; Jia, Lin; Zacks, David N.
ABSTRACT: We describe a protocol for rapid and efficient enrichment of autophagosomes from various tissues of the GFP-LC3 mouse. In order to increase the number of autophagosomes, we block autophagy flux in the GFP-LC3 mouse tissue with a single intraperitoneal injection of leupeptin 4–5 h before tissue harvesting. We homogenize dissected tissue samples using a Dounce homogenizer followed by passing the slurry through needles of different sizes to dissociate the cells and disrupt their outer membranes. The post-nuclear supernatant fraction of the cell lysate is further centrifuged and the supernatant fraction is discarded to remove residual cytosolic GFP-LC3 that is not associated with autophagosomes. The pellet fraction is resuspended and incubated with magnetic microbeads coated with anti-GFP antibodies for 1 h on ice. The lysate-bead mixture is then applied to a column that is placed in a magnetic separator. After washes, the autophagosome fraction is eluted from the column for morphological and protein analysis. Abbreviations : EDTA: ethylenediaminetetraacetic acid; GAPDH: glyceraldehyde 3-phosphate dehydrogenase; GFP: green fluorescent protein; HEPES: 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid; LC3: microtubule-associated protein 1 light chain 3 beta; MES: 4-morpholineethanesulfonic acid (MES); SQSTM1: sequestosome 1; TEM: transmission electron microscopy